The effect of soy milk on increasing hemoglobin levels in adolescent girls with anemia - Ana Mariza; Asih Dwi Astuti; Astriana Astriana; Dessy Hermawan (THE JOURNAL OF Mother and Child Health Concerns, 2025)
Background: Anemia is a common health problem among adolescent girls, primarily due to blood loss during menstruation. This condition can interfere with learning concentration and daily activities. At Waskita Bekri Junior High School (SMP Waskita Bekri), 34 out of 52 female students were identified with mild to moderate anemia a relatively high prevalence, partly caused by a one-year delay in the distribution of iron supplementation tablets. Anemia prevention can be carried out through both pharmacological and non- pharmacological approaches, one of which is the consumption of soy milk. Purpose: To determine the effect of soy milk consumption on increasing hemoglobin levels in adolescent girls with anemia at Waskita Bekri Junior High School, Central Lampung Regency. Method: The study was conducted in May 2025 using a quantitative analytical experimental method with a one- group pretest–posttest design. The sample consisted of 34 female students selected through purposive sampling, based on hemoglobin levels measured using the Easy Touch device, who were identified as having mild to moderate anemia. Data were analyzed using univariate and bivariate methods, with the paired t-test applied for statistical testing. Results: The results showed that the average hemoglobin level before the intervention was 11.12 g/dL, which increased to 12.20 g/dL after soy milk consumption. The mean difference of 1.08 g/dL indicates an improvement in hemoglobin levels following the intervention. Conclusion: The paired t-test yielded a p-value of 0.000 (< 0.05), confirming a significant effect of soy milk consumption on increasing hemoglobin levels in adolescent girls with mild to moderate anemia. Suggestion: It is recommended that adolescent girls at Waskita Bekri Junior High School maintain a balanced diet and regularly consume iron supplements as advised to prevent anemia.